Permafrost existence in the rock glaciers of the Argentera Massif (Maritime Alps, Italy). - RIBOLINI, ADRIANO; FABRE D. (Permafrost and Periglacial Processes, 2006)
Thermal and geo-electrical investigations were carried out on five rock glaciers in the Argentera Massif to detect the presence of permafrost and to define its existence and activity elevation limits. Ground surface temperature was monitored using digital dataloggers, and sub-surface ice occurrence was inferred from one-dimensional geo-electrical soundings. Bottom temperatures of snow cover, extracted from winter recordings, indicate possible or probable presence of permafrost for some rock glaciers. Geo-electrical soundings reveal the existence of sediments rich and super-saturated with ice for thicknesses often reaching several tens of metres. The limits for permafrost existence and for rock glacier activity can thus be fixed respectively at about 2500m and 2600m ASL. The results from 110 earlier geo-electrical soundings, carried out on rock glaciers in different sectors of the southwestern Alps, were processed and compared with the results of this work. A general classification of rock glaciers into active, inactive and relict was possible for the Argentera Massif. Inactive and relict rock glaciers probably originated during colder Holocene and Late-glacial periods.